2014
DOI: 10.1186/1756-3305-7-155
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation on the efficiency of the kit Platelia Dengue NS1 Ag-ELISA to detect dengue virus in dried Aedes aegypti: a potential tool to improve dengue surveillance

Abstract: BackgroundSurveillance is a critical component of any dengue prevention and control programme. Herein, we investigate the efficiency of the commercial kit Platelia Dengue NS1 Ag-ELISA to detect dengue virus (DENV) antigens in Aedes aegypti mosquitoes infected under laboratory conditions.MethodsUnder insectary conditions, four to five day-old mosquitoes were orally challenged with DENV-2 titer of 3.6 x 105 PFU equivalent/ml, incubated for 14 days and then killed. At ten time-points following mosquito death (0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Detecting dengue viral antigens from mosquitoes using antigen detection kits even by public health workers with minimum training has been reported [4952]. In a previous study conducted in an urban area in peninsular Malaysia, we showed that the infected Ae.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Detecting dengue viral antigens from mosquitoes using antigen detection kits even by public health workers with minimum training has been reported [4952]. In a previous study conducted in an urban area in peninsular Malaysia, we showed that the infected Ae.…”
Section: Introductionmentioning
confidence: 70%
“…Sensitivity of NS1 antigen kit on mosquitoes containing the virus has been established to be high (95%) [49]. According to Sylvestre et al [52] the NS1 antigen kit has higher sensitivity compared to the qRT-PCR and virus isolation on dried Aedes mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting observation reported by Thiemmeca et al (22) that NS1 is present in infected mosquito saliva calls for new experiments where the role of NS1, along with mosquito saliva proteins, in virus transmission is evaluated. It is known that NS1 is produced at high levels in infected Aedes aegypti mosquitoes (38)(39)(40), although formal proof that NS1 is actually secreted in vivo by cells in the mosquito is lacking. However, the presence of NS1 in the mosquito saliva suggests that this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Although the role of NS1 protein is not clear, it is known to be important in DENV replication and assembly. 13,15,16 Some experimental data suggest that the NS1 protein is modified by glycosylphosphatidylinositol, and associates with lipid rafts at the plasma membrane, where it mediates signaling. 11,17 Other data suggest that the hexamer may play a role in DHF pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dengue antibodies may crossreact with other flaviviruses, such as YFV, WNV, JEV, SLE, or Zika, which may lead to misdiagnosis by clinicians. 10 At present, there are various diagnostic platforms for DENV NS1 detection such as Platelia dengue NS1 Ag test (Bio-Rad Laboratories, Marnes La Coquette, France), 15,16,19,20 Platelia dengue IgA capture assay (Bio-Rad Laboratories). 21 Pan-E dengue early ELISA test (Panbio Diagnostics, Brisbane, Australia), 19 dot blot immunoassay, 22 DEN antigen detection kit (denKEY Blue kit; Globio Co., Beverly, MA), 22 InBios DENV Detect NS1 ELISA kit 23 Dengue early ELISA (MyBioSource, Vancouver, Canada), DENV NS1 ELISA test kit (EUROIMMUN, Luebeck, Germany), 15,19,[24][25][26] dengue NS1 Ag STRIP (Bio-Rad Laboratories), 27 and NS1 lateral flow rapid test (LFRT).…”
Section: Introductionmentioning
confidence: 99%